Effect of Sodium Metasilicate on Structural, Optical, Dielectric and Mechanical Properties of ADP Crystal. Issue 1 (January 2016) - Anis, Mohd; Shirsat, M.D.; Hussaini, S.S.; Joshi, B.; Muley, G.G.
Highlights: The first to report the effect of sodium metasilicate on properties of ADP crystal. The high optical transparency of SMS-ADP crystal is vital for laser applications. SHG efficiency of SMS-ADP crystal is 2.26(KDP) and 1.25(ADP). Z-scan revealed self-focusing nature of SMS-ADP crystal with χ 3 of order 10 −4  esu. SMS highly improved mechanical and dielectric quality of ADP crystal. Graphical Abstract: Abstract : For the first time, sodium metasilicate (SMS) doped ammonium dihydrogen phosphate (ADP) crystal was grown by slow evaporation solution technique. The unit cell parameters of grown crystal were determined by means of single crystal X-ray diffraction technique. The qualitative analysis of SMS doped ADP crystal was carried out using energy dispersive X-ray and Fourier transform infrared analysis. The increase in optical transparency of doped ADP crystal was ascertained in the range of 200–900 nm using the UV-visible spectral analysis. The vital optical constants were evaluated using the transmittance data to explore various optical device applications of crystal. The assertive influence of SMS on mechanical and dielectric behavior of ADP crystal was investigated by means of Vickers microhardness analysis and dielectric studies, respectively. The enhancement in second harmonic generation (SHG) efficiency of SMS doped ADP crystal with reference to potassium dihydrogen phosphate (KDP) and ADP was confirmed from Kurtz–Perry SHG test. The Kerr lensing nonlinearity in SMS doped ADP crystal was identified by means of Z -scan analysis and the third order nonlinear optical susceptibility (χ 3 ) was found to be 6.19 × 10 −5  esu, which vitalizes its application for laser stabilization systems.